Hybrid vanadate waveguiding configurations for extreme optical confinement and efficient polarization management in the near-infrared. Issue 35 (29th August 2018) - Bian, Yusheng; Kang, Lei; Ren, Qiang; Zheng, Yuanxia; Engel-Herbert, Roman; Werner, Pingjuan L.; Werner, Douglas H.; Jacob, Ajey P.; Thomas, Abu
Abstract : The integration of vanadate materials with planar waveguiding platforms enables novel functional devices with miniaturized footprint and enhanced performance. Abstract : Vanadate materials such as CaVO3 and SrVO3 were recently proposed as promising alternatives to their conventional transparent conducting oxide counterparts owing to the superior capability for simultaneous realization of high optical transparency and high electrical conductivity originating from strong electron–electron interactions. Here we show that, in addition to their remarkable optoelectronic properties as conducting materials, their incorporation into planar waveguiding configurations could enable outstanding optical performance that is otherwise difficult to achieve with conventional material building blocks, especially metals. Starting from the guided wave at a single CaVO3 /dielectric interface, the unique dispersion relationship and propagation property of the fundamental mode are revealed and compared to the conventional surface plasmon polariton associated with a silver/dielectric planar configuration. The superior confinement capability and the unique modal attenuation of the CaVO3 -based waveguiding platform are further demonstrated via investigating silicon-based hybrid guiding schemes integrated with a CaVO3 nanostructure. By leveraging the pronounced polarization dependent loss in the hybrid configuration, an ultra-compact TE-pass polarizer is numerically demonstrated at telecommunication wavelengths. This transformative design features a reduced footprint and enhanced optical performance when benchmarked against the current state-of-the-art in hybrid silicon polarizers. The combination of these vanadate materials with traditional waveguiding platforms thereby opens new avenues towards miniaturized functional integrated photonic devices, and potentially enables a variety of intriguing applications at the sub-diffraction-limited scale.